Pharmacology of heparins and direct anticoagulants - Alban, S (Hämostaseologie, 2008)
For decades, the options for therapeutic anticoagulation were limited to unfractionated heparin (UFH) and vitamin K antagonists (VKA), and their well-known limitations had to be accepted. With the introduction of the various LMWHs, the short- and medium-term anticoagulation could be much improved, but an alternative to VKA is still missing The heparins provided the proof of concept that FXa and thrombin represent suitable targets for therapeutic anticoagulation. Consequently, the search for new anticoagulants focuses on inhibitors of thrombin (DTI) or FXa (DXI). Apart from the VKA, the anticoagulants presently available or in an advanced stage of development can thus be divided in two classes: One are the glyco-anticoagulants with the natural sulfated glycosaminoglycans (GAGs) (UFH, LMWHs, and danaparoid) and the synthetic oligosaccharides (OS) (fondaparinux, idraparinux, and SR123781A). The other class are the xenobiotic anticoagulants, i.e. proteins and synthetic chemical entities. Die glyco-anticoagulants act partially (GAGs) or exclusively (oligosaccharides) by catalysing antithrombin, whereas the xenobiotic anticoagulants are direct inhibitors of either thrombin or FXa. At present, three parenteral DTI (lepirudin, argatroban, and bivalirudin) and since March 2008 one oral DTI (dabigatran etexilate) are clinically used for limited indications. In September 2008 rivaroxaban has been approved as the first oral DXI. This review describes the development of the anticoagualants as well as the pharmacological profile of the clinically used anticoagualants.